Implementing economics subjects within the context of economic kinanthropology - Vladimír Hobza (Palacký University Olomouc, 2014)
BACKGROUND: For more than fifteen years, courses on "Sports Economics" and "Sportkönomie" or "Economics of Sport" - which deal with the interdisciplinary contexts of economics, economics and sport sciences - have been part of a cluster of economic subjects at sport-oriented universities and colleges in EU countries. As of yet, with only a few exceptions, this subject has not appeared in the study programs of Czech universities. This subject is taught at Czech universities in various specific forms only on selected faculties - VŠE Praha, UK in Praha, MU in Brno and UP in Olomouc. OBJECTIVES: The aim of this paper is to describe a new subject, its design, targeting and content. The secondary objective is to highlight the factual reasons for its creation as an immediate response to the many unresolved questions and problems arising from the interdisciplinary relationship between kinanthropology (in the strict sense of the word "movement"), and economics considering theoretical and practical aspects of evaluating the cost-eﬀectiveness of sports activities, grant programs, the eﬀectiveness of the grant process, the eﬀectiveness of sports projects etc. METHODS: The proposal for the course "Economics of Sport" methodically builds on the division of kinanthropology into subspecialties, specifically the subfield of "economic kinanthropology" (Hodaň, 2006). The syllabus of the course is based on an analysis of domestic and foreign literature, analysis of the Czech environment, analyzing primary and secondary data from the sports environment of the country - region - municipality (towns, villages) - sports movements (sport associations and clubs), including analysis of sports bodies and the business environment of sports. RESULTS: The course syllabus prepared is focused on the following priority areas: micro-economic aspects of sport, macro-economic aspects of sport, public economics in sports, the interdisciplinary model of the productive aspect of sports activities, major sporting events and grant issues. This deals progressively with micro and macro-economic issues of sports, sports funding from public sources, projects and grant issues systemically and within the context of the general economic laws. CONCLUSIONS: The article analyzes the reasons for the establishment of a new course entitled "Economics of Sport", the theoretical foundations of the syllabus and its anticipated impact on teaching practice, students' knowledge of the field as well as examining how it contributes to the practical knowledge and managerial-economic skills of graduates of kinanthropologically oriented higher education.